2016
DOI: 10.1186/s12936-016-1101-4
|View full text |Cite
|
Sign up to set email alerts
|

What drives the consistent use of long-lasting insecticidal nets over time? A multi-method qualitative study in mid-western Uganda

Abstract: BackgroundThe distribution of long-lasting insecticidal nets (LLINs) through universal coverage campaigns is a widely adopted approach for the prevention of malaria at scale. While post-distribution surveys play a valuable role in determining cross-sectional levels of LLIN retention and use, as well as frequently cited reasons for non-use, few studies have explored the consistency of LLIN use over time, within the expected lifespan of the net, and the factors which may drive this.MethodsIn this qualitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 29 publications
(25 reference statements)
6
31
0
Order By: Relevance
“…The qualitative findings highlight the locals’ apparent fascination with not just the direct, intended malarial protection benefit, but the collateral benefits including the repelling and killing of all sorts of insects such as bed bugs, fleas, flies, spiders, and other crawlers. Similar findings from a Uganda-based study also show the relevance of this, where Strachan et al [ 14 ] report on the wider benefits of using nets, as experienced by targeted communities, beyond the prevention of malaria. They argued while the protection of malaria remains a powerful motivator, the non-malaria benefits of net use were also found very important in driving consistent use.…”
Section: Discussionsupporting
confidence: 68%
“…The qualitative findings highlight the locals’ apparent fascination with not just the direct, intended malarial protection benefit, but the collateral benefits including the repelling and killing of all sorts of insects such as bed bugs, fleas, flies, spiders, and other crawlers. Similar findings from a Uganda-based study also show the relevance of this, where Strachan et al [ 14 ] report on the wider benefits of using nets, as experienced by targeted communities, beyond the prevention of malaria. They argued while the protection of malaria remains a powerful motivator, the non-malaria benefits of net use were also found very important in driving consistent use.…”
Section: Discussionsupporting
confidence: 68%
“…For example, a study in Gambia showed that privacy obtained by sleeping under a net to be a motivating factor [ 32 ], and in Zanzibar, aspects of comfort appeared to play a key role in personal decisions [ 33 ]. The importance of emphasizing the non-health advantages to sleeping under nets have also been suggested in response to seasonal fluctuations in mosquito numbers which can affect the perceived threat of malaria and, by association, net use [ 8 ]. This evidence suggests future educational campaigns could benefit from advocating non-malaria benefits of net use, in addition to malaria-prevention, to provide a long-term rationale for consistent use.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural components as factors in net use have been found in other countries [46][47][48]. In Loreto, Peru, mosquito net use is integrated into people's habits.…”
Section: Sociocultural Factors In Madagascar and Elsewherementioning
confidence: 96%
“…[55]. In two studies in Uganda and Tanzania, the habit established by "previous positive experiences" of sleeping peacefully was cited as a factor in the development of a "net culture" according to Koenker et al [48,50] and has resulted in "consistent use of LLINs despite uctuations in risk perception" [50].…”
Section: Sociocultural Factors In Madagascar and Elsewherementioning
confidence: 99%